A guide to mediating in Scotland - Malcolm, Ewan A.; O'Donnell, Fiona B. (Dundee : Dundee University Press, 2009)
Mediation is developing in many different areas today throughout Scotland. While some of these may be familiar others are less well known. For the first time, these areas are comprehensively brought together in 'A Guide to Mediating in Scotland'.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Mediation -- Scotland; Law